L'égalité juridique des langues et l'enseignement: les écoles françaises hors Québec - Monnin, Alfred (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
This article examines school language policies currently in effect in all provinces except Quebec. The struggle for linguistic equality has been long and arduous, even in areas where the number of French-speaking residents is considerable. But it is also far from complete. Although some progress has been made, there remains much to be accomplished before the French language school structures outside the province of Quebec can equal English school systems in Quebec.